Disproportionality Among Postsecondary Students Seeking Evaluation to Document Disabilities - Amanda Pellegrino; Beverly Sermons; George Shaver (Disability Studies Quarterly, 2011)
The race/ethnicity disproportionality in identification of special education disability classifications in K-12 education and psychological disorders in the general population has been explored for many years. Other disproportionality trends exist in postsecondary enrollment. However, there is little exploration of the convergence of these phenomena and the representation of students with disabilities in postsecondary education disability service programs. Longitudinal data collected at an evaluation center serving thirteen colleges and universities in Georgia indicate that African-American students are significantly underrepresented in seeking documentation to receive accommodations for disabilities such as learning disabilities, Attention Deficit/Hyperactivity Disorder, and psychological disorders. This trend appears to contradict national trends of proportional representation of reporting disabilities among race/ethnicity groups at postsecondary institutions.
Keywords: Disability; College; and Race/Ethnicity